Management of Multidrug-Resistant Tuberculosis - Daley, Charles L.; Caminero, Jose A. (Seminars in Respiratory and Critical Care Medicine, 2018)
Drug-resistant strains of Mycobacterium tuberculosis pose a major threat to global tuberculosis control. Despite the availability of curative antituberculosis therapy for nearly half a century, inappropriate and inadequate treatment of tuberculosis, as well as unchecked transmission of M. tuberculosis, has resulted in alarming levels of drug-resistant tuberculosis. The World Health Organization (WHO) estimates that there were 600,000 cases of multidrug-resistant tuberculosis (MDR-TB)/rifampin-resistant (RR) tuberculosis in 2016, defined as strains that are resistant to at least isoniazid and rifampicin. Globally, WHO estimates that 4.1% of new tuberculosis cases and 19% of retreatment cases have MDR-TB. By the end of 2016, 123 countries had reported at least one case of extensively drug-resistant strains, which are MDR-TB strains that have acquired additional resistance to fluoroquinolones and at least one second-line injectable. It is estimated that only 22% of all MDR-TB cases are currently receiving therapy. This article reviews the management of MDR/RR-TB and updates recommendations regarding the use of shorter course regimens and new drugs.
Keywords: tuberculosis; drug-resistant tuberculosis; MDR-TB; XDR-TB; management